2009
DOI: 10.1093/humrep/dep393
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance and free androgen index correlate with the outcome of controlled ovarian hyperstimulation in non-PCOS women undergoing IVF

Abstract: Our results suggest a positive correlation of HOMA-IR levels above a threshold level of 2.5 and a continuous positive correlation of free androgen (FAI) to total ovarian follicle count following COH in the non-PCOS patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 37 publications
4
30
0
Order By: Relevance
“…These results suggest for the first time that the down-regulation of aromatase in PCOS may be a result of the hyperandrogenic follicular environment. Consistent with previous studies (Dickerson et al 2010, de Resende et al 2010, Nejad et al 2011, Zhong et al 2012), the present study has shown that PCOS women have similar fertilization rates, good embryo quality rates and clinical pregnancy rates in ART as compared to non-PCOS women (Table 4). A possible reason for this might be that the pituitary suppression treatment necessary for ART have overcome the high LH level in PCOS (Table 3).…”
Section: Discussionsupporting
confidence: 92%
“…These results suggest for the first time that the down-regulation of aromatase in PCOS may be a result of the hyperandrogenic follicular environment. Consistent with previous studies (Dickerson et al 2010, de Resende et al 2010, Nejad et al 2011, Zhong et al 2012), the present study has shown that PCOS women have similar fertilization rates, good embryo quality rates and clinical pregnancy rates in ART as compared to non-PCOS women (Table 4). A possible reason for this might be that the pituitary suppression treatment necessary for ART have overcome the high LH level in PCOS (Table 3).…”
Section: Discussionsupporting
confidence: 92%
“…17,18 Finally, we dichotomized HbA1c% using standardized cut points (< 6.5% as the referent versus ≥ 6.5%). Each of the outcome variables was assessed at baseline, 6 months, and 12 months post-intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Recruitment details and methods have been described previously. 1 In short, 49 women with male factor infertility, without PCOS were recruited preceding an IVF cycle. All women had a regular menstrual cycle and none had polycystic ovaries on ultrasound.…”
Section: Methodsmentioning
confidence: 99%
“…1 The treatment cycle was abandoned if the total follicle count was below 5, above 25 or if other signs/symptoms of ovarian hyperstimulation were observed. Abandoned cycles were not excluded from analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation